A CAD/CAE integration method based on Excel. (2016) - Liu, Xiujuan; Liu, Fuyun; Han, Lu; Liu, Renshun; Li, Kuan
The parametric design technology, parametric CAE analysis technology and Excel unique functions were analysed, and a CAD/CAE integration method based on Excel was proposed. The proposed method can implement CAD/CAE integration automatically and efficiently. In the whole design analysis process, it needs no manual processing. As an example, an output shaft part was used to verify the accuracy and efficiency of the method. Results show that the proposed method has the characteristics of high universality and strong practicability. The proposed method will provide key technology support for us to realise product design efficiently, and to realise variant designs can satisfy engineering constraints.